Estimation of erosion induced nutrients loss under different land uses: A case study in Miandam Valley, Swat Pakistan - Yousaf, Nowsher; Khan, Bushra; Flanagan, Dennis C; Mian, Ishaq Ahmad; Iqbal, Javaid; Rashid, Irfan; Khalid, Salma; Ghaffar, Nasreen; Manzoor, Sadaf; Bilal, Muhammad (International Journal of Agricultural and Biological Engineering, 2021)
In order to design Sustainable Land Management (SLM) plans or interventions it is important to understand the land use change and subsequent impacts. The basic aim of this study was to assess the impact of land use land cover (LULC) change on soil physico-chemical properties and nutrients loss under different land use/land cover changes within Miandam watershed of Swat valley, Pakistan. The study area was divided into three major types on the basis LULC type (Dense forest, Moderate forest and Agriculture land). A total of 81 soil samples were collected from the study area (27 from each land use) through stratified random sampling and were transferred to the laboratory. The prepared soil samples were then tested for various physico-chemical properties such as pH, electrical conductivity, contents of organic matter, organic carbon, sand, silt, clay, nitrogen, phosphorus, potassium, iron, copper and zinc. Results showed that LULC significantly affected all soil parameters except electrical conductivity and potassium. For all the nutrients assessed, the enrichment ratio was greater than 1 which showed that the most fertile layer of the soil in the cropped areas was transported through soil erosion. In this study, time-series satellite images were used to determine the spatiotemporal changes in the LULC of Miandam valley of Swat, Pakistan, and the possible effect of LULC on soil properties was reported. The information generated on the soil properties as indicators of soil health could be used to inform the stakeholders about the effect of LULC change in the study area. Multi-temporal image acquired by Landsat sensors for the year 2018 was used for quantifying changes in the study area. The Landsat images for the year 2018 were classified into six land cover/land use classes. The increase in agricultural activities caused an increase in the land farming areas which led to an increase in the rate of deforestation in the valley. Thus, the present study results reveal that the use of the soil for agriculture instead of keeping them naturally or in other words changes in the land use land cover affects the soil physico-chemical properties and the overall nutrients availability. Keywords: land use/land cover, soil properties, soil nutrients, Miandam, Swat valley DOI: 10.25165/j.ijabe.20211402.5704 Citation: Yousaf N, Khan B, Flanagan D C, Mian I A, Iqbal J, Rashid I, et al. Estimation of erosion induced nutrients loss under different land uses: A case study in Miandam Valley, Swat Pakistan. Int J Agric & Biol Eng, 2021; 14(2): 135–141.